Pentingnya Keteladanan Orangtua Dalam Keluarga Sebagai Dasar Dalam Pembentukan Karakter Masyarakat Jepang (Suatu Tinjauan Etis) - Sri Sudarsih (KIRYOKU, 2019)
(Title: The Importance Of Parents In The Family As The Basis Of Establishment Of Japanese Community Characters(An Ethical Review)) Japan including developed countries in various fields, but the people still maintain tradition. This study aimed to describe parenting in families in Japan. Then the researchers interpreted the importance of parental exemplary in the formation of Japanese society. This research is a literature research on the lives of Japanese society. The method used by researchers is a description and interpretation. The result of this study is described as follows: the example of parents is imperative because parents are a figure for the children. Exemplary is applied in all aspects of live. Family education is the basis for forming individual character. Ethical values are always the basis for behaving. Parenting in the family brings logical consequences to the pattern of individual behavior to the social environment. Ethical values as a basic principle that is applied a close manner in the family environment have formed general awareness. These methods are able to shape Japanese society with a strong character.